Noninvasive Assessment of Schistosoma‐Related Periportal Fibrosis. (15th January 2021) - Hashim, Ahmed; Berzigotti, Annalisa
Abstract : Schistosomiasis affects nearly 250 million individuals in the world. Hepatosplenic schistosomiasis (HSS) results in periportal fibrosis (PPF) and portal hypertension (pHTN). Ultrasound has been extensively used for the diagnosis of Schistosoma ‐related PPF and a number of staging methods have been validated for this purpose such as Strickland classification and Niamey protocol. Nevertheless, the application of noninvasive techniques, particularly elastography modalities, has not been well explored. In this review, we describe the various noninvasive diagnostic tools for assessment of Schistosoma ‐related PPF including US parameters, serum biomarkers, and US‐based elastography techniques. While elastography techniques have demonstrated value in the evaluation of HSS, the evidence remains limited with most studies recruiting a small number of patients. Longitudinal studies with larger sample size are required in order to devise robust criteria to accurately assess the performance of noninvasive techniques in the prediction of both regression and progression of the degree of PPF and identify their cost‐effectiveness in community screening.